2016
DOI: 10.1242/jeb.127829
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension dominates insect flight on fluid interfaces

Abstract: Flight on the 2D air-water interface, with body weight supported by surface tension, is a unique locomotion strategy well adapted for the environmental niche on the surface of water. Although previously described in aquatic insects like stoneflies, the biomechanics of interfacial flight has never been analysed. Here, we report interfacial flight as an adapted behaviour in waterlily beetles (Galerucella nymphaeae) which are also dexterous airborne fliers. We present the first quantitative biomechanical model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…The high body angles (x) during dragonfly backward flight parallels similar observations of hummingbird [13] and insect backward flight [11] and could be a mechanism of convergent evolution [13]. However, x was significantly larger than those of hummingbirds (50-758) which use a horizontal stroke plane and waterlily beetles (50-708), which use an inclined stroke plane [13,38]. Our x corroborated previous observation in dragonfly backward flight (1008) [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high body angles (x) during dragonfly backward flight parallels similar observations of hummingbird [13] and insect backward flight [11] and could be a mechanism of convergent evolution [13]. However, x was significantly larger than those of hummingbirds (50-758) which use a horizontal stroke plane and waterlily beetles (50-708), which use an inclined stroke plane [13,38]. Our x corroborated previous observation in dragonfly backward flight (1008) [11].…”
Section: Discussionsupporting
confidence: 89%
“…Rü ppell [11] recorded a dragonfly flying backward with a body angle of 1008 from the horizon. Likewise, Mukundarajan et al [38] reported that a stroke plane tilted backward, and a steep body angle between 508 and 708 from the horizontal induced backward flight in waterlily beetles (Galerucella nymphaeae). Our observations corroborate these reports as we consistently witnessed an upright body posture during the backward flight of dragonflies in our experiment.…”
Section: Introductionmentioning
confidence: 96%
“…Most solid substrates are microscopically rough. This microscopic roughness can lead to superwettability, since the surface tension effect dominates over the gravitational effect at the microscale . Surface roughness or defects on solid substrates can help pin a contact line for an advancing drop.…”
Section: Design Principles and Mechanisms: Learning From Naturementioning
confidence: 99%
“…Macroscopic swimmers embedded in a rotating fluid will exhibit inertial effects on top of the frictional ones. One example are waterlily beetles moving near the two-dimensional water-air interface [36].…”
Section: Experimental Verification Of the Predictionsmentioning
confidence: 99%